The 'Alternative for Germany': The rise of right-wing populism at the heart of Europe. (August 2018) - Lees, Charles
This article charts the rise of the 'Alternative for Germany' ( Alternative für Deutschland or AfD) from its inception in late 2012 to its unexpectedly strong performance in the 2017 Federal election. In terms of the 'inward' aspect of Euroscepticism, the article considers the impact of the emergence of successively more hardline leaderships in 2015 and 2017, which led to a shift beyond opposition to aspects of the European integration process to a more profound critique of German society and politics. In terms of the 'outward' aspect, it assesses the significance of these developments in the wider debates around Euroscepticism and populism. The article concludes that the AfD's Euroscepticism is now nested within an ideological profile that increasingly conforms to the template of an orthodox European right-wing populist party. It argues that the widely unanticipated level of electoral support for the AfD in the 2017 Federal elections and its status as the main opposition party in the Bundestag is a systemic shock and potential critical juncture in the development of the German party system and the contestation of European integration in the Federal Republic.